What are the Obstacles in Achieving Ideal Family Size in Reproductive Age Couples? - Dian Jayantari Putri K. Hedo; Nicholas Simarmata (Media Kesehatan Masyarakat Indonesia, 2022)
The world situation with full of demands and limitations during the current pandemic can bring negative impacts on family. Family face burdens of daily needs for family life’s. Regarding to this condition, the ideal family size which is couple who has no more than two children, is an entity that needs to be considered to ensure the survivability of family. This study aimed to determine factors that related and predict the ideal family size for reproductive age couples in East Java. This study was quantitative study with cross-sectional approach. Data used in this study was secondary data from the Family Data Collection in 2021. Sampling technique was saturation sampling on reproductive age couples in 38 cities and regencies of East Java. Dependent variable was ideal family size. Independent variable was ideal age of marriage, participation in modern contraception, preferences for the ideal number of children, exposure to electronic media information, exposure to social media information, exposure to printed media information, and exposure to mass media information. Data analysis used multiple linear regression test. The study result stated variables that were related and had contribution in predicting ideal family size in reproductive age couples were ideal marriage age (p=0.001), participation in modern contraception (p=0.001), preference for ideal number of children (p=0.001), exposure to electronic media information (p=0.018), and exposure to mass media information (p=0.009). Based on these results, it is hoped that several intervention programs can be arranged by related institutions, targeted in the field that are in accordance with the study results.